The effect of wine tourism experiences on wine brands - Correia, Ricardo (2014)
Wine tourism takes on a clear hedonic dimension, being especially prone to the design of experiences. The characteristics of wine tourism makes this product quite compatible with the predominantly rural areas of the several tourist proposals thus seen as a higher capacity of sustainable development. Most of the studies that characterize the wine tourism experiences have a clear focus on the demand side. This paper aims at obtaining a greater insight into the leverage of the wine brands through positive experiences associated with wine tourism. It is therefore essential to the understanding of this point to measure the perception of wine tourism entrepreneurs about the variables that change, influence and lead the consumer to act. Sustained on the Grounded Theory, a deep analysis of the perception that the cellars/farms have about the effect of their touristic offer on their wine brands was carried out. Although there is no use of concrete measures on the supply-side, there is the conviction of a reciprocal leverage effect between wine tourism experiences and wine brands.